Stochastic Dominance Rules for Multi-attribute Utility Functions - Huang, C. C.; Kira, D.; Vertinsky, I. (Review of Economic Studies, 1978)
C. C. Huang, D. Kira, I. Vertinsky; Stochastic Dominance Rules for Multi-attribute Utility Functions, The Review of Economic Studies, Volume 45, Issue 3, 1